Metaphorical processes as basis of proper names - Brozović Rončević, Dunja; Žic Fuchs, Milena (2005)
One of the major 'innovations' Cognitive linguistics introduces is the re-evaluation and re-interpretation of the traditional linguistic notions of metaphor and metonymy. Everyday, conventional metaphors have for centuries been considered to be 'dead' metaphors, and thus not worth analysing. Cognitive linguists on the other hand consider them to be the most lively and the most productive part of language, or as Lakoff and Turner (1989: XI) claim: « Metaphor is a tool so ordinary that we use it unconsciously and automatically, with so little effort that we hardly notice it.» Although research on metaphor and metonymy has been very intensive within cognitive linguistics during the last fifteen years, so far this approach has not been applied to onomastic data. Therefore, the aim of this paper is to analyse how productive the cognitive linguistic view of metaphor can be in research of the primary creation of proper names, more specifically in the creation of first names. Data from Croatian will be analysed, particularly names related to vuk – wolf and medvjed – bear, names that go back a long way in Croatian history. This data will be compared to that of other European languages.
Projekt MZOS
Projekt MZOS
ENG